Prevalence and Impact of Atrial Fibrillation on Prognosis in Takotsubo Cardiomyopathy Patients. (October 2022) - Koniari, Ioanna; Papageorgiou, Angeliki; Artopoulou, Eleni; Velissaris, Dimitrios; Mplani, Virginia; Kounis, Nicholas; Hahalis, George; Tsigkas, Grigorios
The purpose of this review is to describe the impact of atrial fibrillation (AF) on the cardiovascular outcomes and prognosis in patients with Takotsubo Cardiomyopathy (TTC). The pathophysiological basis of TTC is set on the release of catecholamines, occurring post an emotional or stressful event. The cardiovascular system of patients with TTC is affected by the high concentrations of catecholamines, creating the ideal background for the development of AF: inflammation, myocardial stress, and excessive sympathetic activity. AF is considered to be the most frequent arrhythmia in TTC patients and is associated with higher rates of cardiovascular and all-cause mortality. AF is also linked with a worse prognosis concerning the hemodynamic status, cardiac fibrosis, lethal arrhythmias, thromboembolic events, and adverse heart failure associated outcomes. The early diagnosis of AF in these patients plays significant role in the prevention of adverse events, the reversibility of left ventricular function, and the restoration of sinus rhythm.